Interactive Learning Videos Based on Problem-Based Learning in Mathematics for Eighth Graders - Shelfy Nasfovi; Desak Putu Parmiti (Jurnal Edutech Undiksha, 2023)
Learning in schools is still centred on the teacher and uses conventional media to make students less active, decreasing their interest and learning outcomes. This study aims to develop problem-based learning interactive learning videos in the Mathematics subject of eighth-grade students. The development model used is the ADDIE model. The subjects of this study were 28 eighth-grade students using questionnaires and tests—data analysis techniques using descriptive qualitative analysis, quantitative, and inferential statistics. The results showed that the results of the validity of the expert test (content, design, and media) obtained an average score of 94.82% (very good qualification), and individual, small group and field tests obtained an average score of 88.66 (good qualification). The t-test results stated significant differences in student learning outcomes before and after participating in learning using problem-based learning and interactive video learning. This interactive learning video can make students more active and increase student interest and learning outcomes, as well as open insights and hone teachers' abilities to utilize technology in making learning media interesting, effective, and varied.